Lingual function in children with anterior open bite: A case-control study (2023)
The position of the tongue during phonation and swallowing can modify the position of the teeth and even the growth of the jaws. Objective: To determine the association between the position of the tongue and phonation among individuals with normal vertical overbite (NVO) and anterior open bite (AOB). Materials and methods: This was a case-control study of 132 students with AOB and 132 controls with NVO between the ages of 8 and 16 years old. The presence of AOB was determined during a clinical examination using a Boley gauge, phonation (speech) was assessed with an articulation test, which was analysed using a classification table of Spanish consonants spoken in Colombia, and tongue contact during swallowing was determined with the Payne test. Associations were determined between AOB and the position of the tongue upon swallowing and during speech (Chi2 test of independence, Fisher's exact test, and Mann-Whitey U test, P < 0.005). Finally, a logistic regression model was performed, with AOB as the dependent variable. Results: We found associations between AOB and the presence of lingual interposition, distortion, lingual thrust, protrusion of the tongue, contact with palatine rugae, and type of dentition (P < 0.05). According to the logistic regression model, the presence of lingual thrust (odds ratio (OR): 0.067; 95% confidence interval (CI): 0.009–0.518) and contact with the palatine rugae (OR: 0.420; 0.216–0.818) behave as protective factors associated with the presence of AOB, and the presence of distortion was found to be a risk factor (OR: 10.751; 95%CI: 5.658–20.427). Conclusion: Lingual thrust, interposition, and protrusion are associated with AOB. Lingual thrust and contact of the tongue with the palatine rugae behave as protective factors, and the presence of distortion acts as a risk factor. © 2018